Achieving protection against HBV in HIV patients: Finding the best strategy. Issue 12 (1st December 2016) - Vargas, Jose Ignacio; Arab, Juan Pablo; Jensen, Daniela; Fuster, Francisco
ABSTRACT: HBV and HIV coinfection is common and entails important morbi-mortality. Vaccination and anti-HBs seroconvertion is a desirable goal in HIV infected patients. New strategies are necessary to predict seroconversion and clinical endpoints. More studies, in the subgroup of HIV patients with poor immunovirological status are needed.